The moral duty to help others from a Kantian perspective. Part І. The theoretical landscape of the study - Маслікова, Ірина (Ukrainian Cultural Studies, 2024)
Background. The article notes the importance of turning to Kantian ethics to clarify the possibilities of fulfilling the moral duty to help others. Such a formulation of the problem sharpens the ethical issues of the emergence of moral duties, their nature and moral force, and the possibilities of performing exceptional extremely sacrificial acts for the sake of others in extreme situations. The goal of the article is to identify the nature, strength and effectiveness of the moral duty to help others from the perspective of Kant's deontological ethics. The first part of the article aims at outlining the theoretical landscape of the study and identifying theoretical issues of substantiating the moral duty to help others. The goal of the second part will be to identify the practical problems of implementing the moral duty to help others.Methods. The article uses the historical and philosophical method to define the basic ethical terminology of deontological ethics and the typological method to clarify the classification of moral duties and moral acts aimed at helping others.Results. The starting point of the study is the understanding of duty as a subjective basis for the effectiveness of the moral law through self-compulsion and as an end that a person sets for himself or herself. In this sense, the duty to help others is actualised in the subject's awareness of the need to promote the happiness of others as his or her own goal. The duty to help others is viewed through the prism of the Kantian typology of 'broad' or 'imperfect' and 'narrow' or 'perfect' duties, which allows us to see the impossibility of setting limits to its implementation, since it is rather a minimum moral claim due to its essential characteristic of 'imperfection'. Its latitude provides room for moral choice, taking into account various moral considerations. The limiting factor in its implementation is the requirement of respect for the other and the prohibition of indifference to the needs of others. It is outlined the main discussion points around the duty to help other, which are related to the threats of devaluation of the moral subject's own interests and the problem of supererogation of certain actions that have moral value but are not morally obligatory.Conclusions. Deontological ethics can be modernised by introducing into its system moral acts which can be defined as exceptional in their ability to help others due to the extraordinary virtues and extraordinary volitional efforts of the moral agent. Such a modification is possible because Kantian ethics orientates the individual towards both help others and his or her own improvement.
Keywords: moral duty; helping others; beneficence; Kantian ethics; deontological ethics; Supererogation